The Effects of Net Profit Margin, Debt Ratio, Total Assets Turnover, and Current Ratio on the Stock Prices of IDX 30 Companies within 2018-2022 - Nicko Albart; Hadi Purnomo; Ujang Suherman; Loso Judijanto; Sri Hermuningsih (GoAcademica Research & Publishing, 2023)
This research delves into the intricate relationship between financial metrics and stock prices within the Indonesian market context. Analyzing data from IDX 30 companies over the period 2018-2022, the study focuses on net profit margin, debt ratio, total assets turnover, and current ratio as key variables. The findings reveal that net profit margin exerts a positive significant influence on stock prices, highlighting the allure of profitable companies to investors. Conversely, the current ratio exhibits a negative impact, indicating the nuanced interplay between liquidity and stock valuation. Notably, total assets turnover does not significantly influence stock prices, emphasizing the multifaceted nature of investment decisions. Additionally, the study underscores the adverse effect of higher debt ratios on stock prices, reflecting investor concerns about financial leverage. These insights offer valuable implications for investors, analysts, and policymakers, enhancing our understanding of the Indonesian stock market dynamics and aiding in strategic investment planning.